2008
DOI: 10.1111/j.1939-1676.2008.0191.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Thyrotropin Administration Enhances Thyroid Uptake of Radioactive Iodine in Hyperthyroid Cats

Abstract: Background: Hyperthyroidism is the most diagnosed endocrine disorder in cats and radioiodine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
12
2
Order By: Relevance
“…I n humans with multinodular goiter and thyroid cancer, recombinant human thyroid stimulating hormone (rhTSH) increases radioactive iodine thyroid uptake, allowing 131 I dose reduction, lower radiation‐absorbed doses by extrathyroidal organs and tissues, and higher treatment efficacy 1−4 . rhTSH also increases radioactive iodine thyroid uptake in the rhesus monkey and in hyperthyroid cats 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I n humans with multinodular goiter and thyroid cancer, recombinant human thyroid stimulating hormone (rhTSH) increases radioactive iodine thyroid uptake, allowing 131 I dose reduction, lower radiation‐absorbed doses by extrathyroidal organs and tissues, and higher treatment efficacy 1−4 . rhTSH also increases radioactive iodine thyroid uptake in the rhesus monkey and in hyperthyroid cats 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…1À4 rhTSH also increases radioactive iodine thyroid uptake in the rhesus monkey and in hyperthyroid cats. 5,6 The use of rhTSH in thyroid carcinoma patients raises important safety issues. In humans, rhTSH increases the volume of the thyroid gland in healthy subjects 7,8 and causes expansion of primary thyroid tumors and thyroid tumor metastases.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the lack of effect of rhTSH in hyperthyroid patients may be caused by decreased thyroid functional reserve. This seems, however, less likely because in hyperthyroid cats and in humans with toxic nodular goiter (a condition characterized by nodular enlargement of the thyroid gland and hyperthyroidism), a significant increase in thyroid RAIU is observed after rhTSH administration [18], [37].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in this study 123 I was chosen as an imaging agent, despite its high cost. Recent pilot studies performed by our group have already investigated the use of rhTSH to optimize the uptake of radioiodine-123 ( 123 I) in healthy dogs and hyperthyroid cats [17], [18]. The goal of this study was to evaluate the effect of 100 μg rhTSH, administered IV 24 h before 123 I, on tumor RAIU in dogs with thyroid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…12 In a small pilot study of hyperthyroid cats, RAIU was increased by administration of 25 μg rh-TSH, but changes were heterogeneous and of questionable clinical utility. 13 The authors speculated that increased rh-TSH doses could have resulted in greater and more consistent increases in RAIU. 13 Indeed, an in vitro study has shown that responsiveness of feline thyroid cells to TSH is dose dependent, and hyperthyroid cells require higher TSH concentrations than do normal cells to stimulate cellular activity and thyroglobulin expression.…”
Section: Introductionmentioning
confidence: 99%